Iterative decoding for MIMO channels via modified sphere decoding. - Vikalo, H.
In recent years, soft iterative decoding techniques have been shown to greatly improve the bit error rate performance of various communication systems. For multiantenna systems employing space-time codes, however, it is not clear what is the best way to obtain the soft information required of the iterative scheme with low complexity. In this paper, we propose a modification of the Fincke-Pohst (sphere decoding) algorithm to estimate the maximum a posteriori probability of the received symbol sequence. The new algorithm solves a nonlinear integer least squares problem and, over a wide range of rates and signal-to-noise ratios, has polynomial-time complexity. Performance of the algorithm, combined with convolutional, turbo, and low-density parity check codes, is demonstrated on several multiantenna channels. The results for systems that employ space-time modulation schemes seem to indicate that the best performing schemes are those that support the highest mutual information between the transmitted and received signals, rather than the best diversity gain.
Keywords: BER performance; MIMO channel; Bit error rate; Computational complexity; Convolutional code; Iterative decoding technique; Low-density parity check code; Maximum a posteriori probability estimation; Modified sphere decoding algorithm; Multiantenna channel; Space-time code; Space-time modulation scheme; Turbo code; Wireless communication